DAMPAK KURS, PRODUK DOMESTIK BRUTO DAN INFLASI TERHADAP HARGA SAHAM JAKARTA ISLAMIC INDEX PERIODE 2007-2019 - Fikrie Lazuardi Imaduddin, - (2020)
The presence of the capital market in Indonesia adds many alternative investment instruments in the form of securities for investors to invest their excess funds. Stock is one of them. Macroeconomic conditions are one of the factors that can influence stock price movements. This study will try to reveal the correlation between exchange rate, GDP and inflation in Indonesia by using panel data regression analysis and using secondary data for 50 periods from 2007 to 2019. Macroeconomics variables used are exchange rate, GDP, and inflation. This research is an explanatory research with a quantitative approach. The results of the hypothesis using panel data regression analysis show that exchange rate has significant negative effect on JII, GDP testing has a significant positive effect, and inflation has a significant negative effect.